3D seismic structural characterization of faulted subsurface reservoirs in the northern East Cameron Block, Gulf of America continental shelf: implications for CO2 sequestration - O’Donnell, Madeleine; Anyiam, Obinna Chinanuekpere; Anyiam, Uzonna Okenna; Uzuegbu, Emmanuel Ebuka; Hughes, Makenna; Beaty, David; Bodunde, Segun Steven; Osotuyi, Abayomi Gaius; Kagaju, Rita; Dickey, Carter; Penniall, Samuel; Bauer, Cherokee (Frontiers in Earth Science, 2025)
Widespread deployment of carbon capture and storage (CCS) technology depends on the ability to safely and effectively store carbon dioxide (CO2) in deep geological formations. However, overlying sedimentary sequences obscure the structural and stratigraphic framework, affecting volumetric capacity assessment in the northern Gulf of America (GOA). In the East Cameron Block, located 40 km offshore Louisiana, we assess the key factors controlling CO2 storage viability by unraveling the morphology of reservoir formations and regional sealing units using 3D seismic data, well-log analysis, structural modeling, and volumetric analysis, to develop structural models and trapping mechanisms that will enhance CO2 sequestration in the Miocene to Pliocene reservoirs of the GOA. Our results reveal the northern GOA continental shelf reservoirs to be predominantly characterized by growth fault bounded faulted rollover anticlines and a massive salt-cored northeast-southwest trending anticline associated with crystal collapse faults that segment the reservoirs in the north. Strata in the northern GOA shelf are interpreted to have been deformed by extension in the coastal region of the contractional salt-related folds and secondarily by salt diapirs and inflation of the anticline by the flow of the ductile and overpressured marine salts. In general, thick columns of clay stones and shales overlie the Miocene to Pliocene sandstone reservoirs, serving as widespread regional seals for the reservoirs. Analysis of the structural maps of the interpreted target reservoirs revealed over 20 structural closures that are favorable storage complexes for commercial CO2 sequestration, with a total storage capacity of ∼70 million metric tons of supercritical CO2. These integrated analyses demonstrate that the characterization of structural geometry, stratigraphic framework, and volumetric potential of Gulf Coast storage complexes play a critical role in determining the long-term viability of CCS in the region.